Secession or solidarity: Catalonia will not get both simultaneously - Sabine Riedel (Stiftung Wissenschaft und Politik (SWP), 2018)
Since the arrest of the former head of the Catalan government, Carles Puigdemont, a solidarity movement has emerged that paints him as a victim of the justice system. However, even if the German government prevents his extradition this is hardly likely to influence the trials against his colleagues remanded in custody in Madrid. The Spanish public prosecutor's office accuses them not only of rebellion, but also of embezzling money from the autonomous communities' liquidity fund (FLA) for their independence campaign. Since the 2012 financial crisis, Madrid has had to subsidise heavily indebted regions, including Catalonia, with loans. Barcelona annually receives between 6.7 billion (2012) and 11.1 billion euros (2015). This financial dependence motivates Catalans to bid for independence, in the expectation that it will lead to direct access to the European Central Bank (ECB). Europeans need to reflect on who should be given their solidarity. A Catalan state would be born with a mountain of debt, which the other Spanish regions and the European taxpayer would ultimately have to shoulder.
Keywords: 320